Simulação numérica do escoamento em difusores radiais com discos frontais fixos e móveis - Maia, Leticia Irene Guimarães [UNESP] (2015)
The flow description in suction and discharge valves used in refrigeration compressors is very complex. Therefore, the valves have been studied through simpler models as the radial diffuser. The static configuration, which disregards the movement of the frontal disc, has been widely studied and has produced important contributions to the development of valves designs. However, the real problem is characterized by a strong fluid-structure interaction due to the coupling between the fluid flow and the dynamics of the frontal disc. A gap in the literature is the absence of studies on the numerical simulation of this fluid-structure interaction problem as the experimental validation is the main concern. In this work, the flow through radial diffusers with static and moving frontal discs are numerical investigated using a commercial code based on the Finite Volume method (Fluent version 15.0) aiming at analyzing in details the main characteristics of the flow. Firstly, the flow through a radial diffuser with static frontal disc and diameter ratio of D/d=1.5 was studied. The numerical methodology was experimentally validated for Reynolds numbers varying from 4,000 to 20,000 and distances between discs in the range of s/d=0.01 to s/d=0.09. Then, the same basic geometry was used to study the fluid-structure interaction problem, in which the dynamics of the frontal disc was modeled as a one degree of freedom mass-spring-damping system. The numerical methodology was validated with experimental data for Reynolds numbers around 2,000, considering two stiffness systems. The obtained results show that both methodologies can be considered partially validated ...